Evaluation of immunity against poliovirus serotypes among children in riverine areas of Delta state, Nigeria. (2011)
"Nigeria remains one of the major reservoirs for wild poliovirus transmission despite the reported success in National Immunization Days and acute flaccid paralysis surveillance. Two hundred children aged ≤ 10 years, were enrolled following parental consent from hard-to-reach riverine areas of Delta state of Nigeria to assess the level of protective immunity to poliovirus. Neutralizing antibodies to the three poliovirus serotypes in the serum samples of the children were determined by the beta method of neutralization. Eight (4%) of the children had no detectable antibody, 178 (89%), 180 (90%) and 181 (90.5%) were positive for antibodies to poliovirus types 1, 2 and 3, respectively. Overall, 162 (81%) of the children had antibodies to the three poliovirus serotypes at a titre of at least 1:8. The study shows the need for proper monitoring of vaccination coverage in such hard-to-reach riverine areas to achieve the objective of the global eradication of poliovirus."